Pengaruh Kepemimpinan Transformasional, Motivasi Kerja, dan Budaya Kerja Terhadap Kinerja Guru SMP Negeri - Miharja, Thalita Salsabila; Vincent Didiek Wiet Aryanto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Education is a human effort to develop their knowledge through the formation of attitudes, values and behavior. Teachers play an important role in the educational process and their performance is very important to create quality students. Because various factors, including work culture, workplace motivation, and transformational leadership, influence teacher effectiveness. Consequently, the aim of this study was to determine whether these factors significantly influence teacher performance. This research was conducted using quantitative methods at State Middle Schools in Tegal City. This research involved most of the state junior high school teachers in Tegal City, with 130 teachers as the target sample. Smart PLS (Partial Least Square) software is the data analysis technique that will be used. The research results show that the transformational leadership variable does not significantly influence teacher performance. On the other hand, work motivation and work culture variables influence teacher performance significantly.